2015
DOI: 10.15835/nbha4319939
|View full text |Cite
|
Sign up to set email alerts
|

The Productivity and Quality of Alfalfa (Medicago sativa L.) in Romanian Forest Steppe

Abstract: Alternative use of alfalfa, for various purposes, including the production of biofuels or food supplement for human alimentation, is a study topic still in its early stages of research. Studying and understanding the biology of alfalfa and the factors with a major influence on it are very important activities. The productivity and quality of alfalfa are two indicators that help determine, in addition to economic value, the way in which alfalfa can be used. Evolution of alfalfa yield and quality depends on many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
3
3
0
Order By: Relevance
“…With an average moisture content of 47.8%, we calculated that total dry shoot biomass varied from 22.5 to 39.8 t per hectare. These results were similar to those reported by Rawate and Hill [37] (dry mass of 25 t per hectare) and comparable with those of the forage crop alfalfa, which yields around 25 t per hectare [38].…”
Section: Discussionsupporting
confidence: 91%
“…With an average moisture content of 47.8%, we calculated that total dry shoot biomass varied from 22.5 to 39.8 t per hectare. These results were similar to those reported by Rawate and Hill [37] (dry mass of 25 t per hectare) and comparable with those of the forage crop alfalfa, which yields around 25 t per hectare [38].…”
Section: Discussionsupporting
confidence: 91%
“…It is known that when plants reach a certain size, they shift energy into forming flower primordial as a result of physiological processes, which are characterized by a decrease in growth activity. Plant height growth rate in this research similar to research done by Stavarache et al (2015) found that plant height increases during plant development with a tendency to stabilize, starting from the beginning of flowering until the harvest time.…”
Section: Discussionsupporting
confidence: 85%
“…Subsequently, some parameters were modified to improve prediction of CP based on literature values (Hintz and Albrecht, 1991;Milić et al, 2011) and by comparison of simulated and measured CP in herbage. For instance, protein concentration in leaf (PROLFI), stem (PROSTI), root (PRORTI), and storage (PROSRI) for tissue grown under luxurious supply of N were based on literature values (Milić et al, 2011;Stavarache et al, 2015). Related tissue parameter modifications are presented in the Table 4.…”
Section: Alfalfa Tissue Compositionmentioning
confidence: 99%
“…Related tissue parameter modifications are presented in the Table 4. The following parameters such as lipid concentration in leaf (PLIPLF), in stem (PLIPST), mineral concentration in leaf (PMINLF), in stem (PMINST), and lignin in leaf (PLIGLF) and stem (PLIGST), were based on the following references (Fox et al, 1991;Stavarache et al (2015) and Teixeira et al, 2007).…”
Section: Alfalfa Tissue Compositionmentioning
confidence: 99%